2016
DOI: 10.1016/j.biopsych.2015.12.016
|View full text |Cite
|
Sign up to set email alerts
|

A Human Open Field Test Reveals Thigmotaxis Related to Agoraphobic Fear

Abstract: This study is the first to our knowledge to verify the translational validity of the OFT and to reveal that thigmotaxis, an evolutionarily adaptive behavior shown by most species, is related to agoraphobia, a pathologic fear of open spaces, and anxiety sensitivity, a risk factor for agoraphobia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 25 publications
3
75
1
1
Order By: Relevance
“…Consistent with our findings in humans and extending the known phenotype of the spastic mouse, we showed that partial Glrb knock-out mice exhibited avoidance of a novel open space, a behavior we recently confirmed to be related to agoraphobic fear in humans 3 . At the mechanistic level, it is somewhat puzzling that the phenotype-associated rs7688285 A allele in fact was not found with decreased, but instead increased GLRB expression in a heterologous cell system as well as in post mortem samples.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with our findings in humans and extending the known phenotype of the spastic mouse, we showed that partial Glrb knock-out mice exhibited avoidance of a novel open space, a behavior we recently confirmed to be related to agoraphobic fear in humans 3 . At the mechanistic level, it is somewhat puzzling that the phenotype-associated rs7688285 A allele in fact was not found with decreased, but instead increased GLRB expression in a heterologous cell system as well as in post mortem samples.…”
Section: Discussionsupporting
confidence: 91%
“…AG is a clinical condition characterized by abnormal open space behavior 3 and, importantly, distorted cognitive processes 4 thus reflecting a dimensional phenotype which can be assessed with the Agoraphobic Cognitions Questionnaire (ACQ) 5 . Family studies reveal familial aggregation in PD and AG 6,7 and twin studies estimated heritabilities of about 38% and 48%, with a genetic correlation of 0.83 between both disorders 8 .…”
Section: Introductionmentioning
confidence: 99%
“…This behavior has been identified in teleosts(Ahmad and Richardson, 2013), rodents(Simon et al, 1994), and in humans (Walz et al, 2015). It is thought that thigmotaxis is a way of finding shelter, protection or a way of escape from a predator or stressor (Sharma et al, 2009).…”
Section: Methodsmentioning
confidence: 98%
“…In this issue of Biological Psychiatry , Walz et al . (1) present results of a human analog paradigm to the rodent open field test (OFT) (2) to quantitatively measure the proclivity for avoidance of open spaces, the core symptom of agoraphobia.…”
mentioning
confidence: 99%